Exploratory study of risk-taking and self-harm behaviours in adolescents: prevalence, characteristics and its relationship to attachment styles - Paiva, A C (2014)
Introduction: Risk-taking (RT) and self-harm (SH) occur across the lifespan, but many types of RT and SH typically appear for the first time in adolescence. According to Vrouva, Fonagy, and Fearon (2010), it is important to measure RT and SH simultaneously because they are clinically, empirically, and conceptually linked. Objectives: (1) analyse the prevalence of risk-taking and self-harm behaviours in community adolescents, controlling the effect of gender and age; (2) examine the link between RT and SH behaviours; (3) investigate the relationship between attachment style and RT and SH behaviours. Methods: 346 adolescents (girls: n = 194, 56%) aged between 12 and 18 years (M = 15.10, SD = 1.77) completed a sociodemographic questionnaire, the Risk-Taking and Self-Harm Inventory for Adolescents (RTSHIA) and the Attachment Questionnaire for Children (AQ-C). Results: RT behaviours more prevalent are taking chances while doing one's hobbies, smoking tobacco and cheating. SH behaviours more frequent are self-demeaning thoughts and behaviours intentionally. Boys showed higher RT behaviours than girls. There is a positive association between age and both behaviours (RT and SH). Insecurely attached teenagers reported higher SH behaviours than did securely attached adolescents. Conclusions: This study shows the prevalence of RT and SH behaviours in a community sample of adolescents, showing how gender and age can influence the expression of both behaviors. It seems that secure attachment may be protective to the engagement in SH behaviors, strengthening the important role of quality of relationships on psychological adjustment in adolescents